Update on gut microbiota in cardiovascular diseases - Qian, Buyun; Zhang, Kaiyu; Li, Yuan; Sun, Kangyun (Frontiers in Cellular and Infection Microbiology, 2022)
In recent years, due to the development and widespread utilization of metagenomic sequencing and metabolomics, the relationship between gut microbiota and human cardiovascular diseases (CVDs) has received extensive attention. A growing number of studies have shown a strong relationship between gut microbiota and CVDs, such as coronary atherosclerosis, hypertension (HTN) and heart failure (HF). It has also been revealed that intestinal flora-related metabolites, such as trimethylamine-N-oxide (TMAO), short-chain fatty acids (SCFA) and bile acids (BAs), are also related to the development, prevention, treatment and prognosis of CVDs. In this review, we presented and summarized the recent findings on the relationship between gut microbiota and CVDs, and concluded several currently known gut microbiota-related metabolites and the occurrence and development of CVDs.